Intestinal microbiota determines development of non-alcoholic fatty liver disease in mice. Issue 12 (29th November 2012) - Le Roy, Tiphaine; Llopis, Marta; Lepage, Patricia; Bruneau, Aurélia; Rabot, Sylvie; Bevilacqua, Claudia; Martin, Patrice; Philippe, Catherine; Walker, Francine; Bado, André; Perlemuter, Gabriel; Cassard-Doulcier, Anne-Marie; et al.
Abstract : Objective: Non-alcoholic fatty liver disease (NAFLD) is prevalent among obese people and is considered the hepatic manifestation of metabolic syndrome. However, not all obese individuals develop NAFLD. Our objective was to demonstrate the role of the gut microbiota in NAFLD development using transplantation experiments in mice. Design: Two donor C57BL/6J mice were selected on the basis of their responses to a high-fat diet (HFD). Although both mice displayed similar body weight gain, one mouse, called the 'responder', developed hyperglycaemia and had a high plasma concentration of pro-inflammatory cytokines. The other, called a 'non-responder', was normoglycaemic and had a lower level of systemic inflammation. Germ-free mice were colonised with intestinal microbiota from either the responder or the non-responder and then fed the same HFD. Results: Mice that received microbiota from different donors developed comparable obesity on the HFD. The responder-receiver (RR) group developed fasting hyperglycaemia and insulinaemia, whereas the non-responder-receiver (NRR) group remained normoglycaemic. In contrast to NRR mice, RR mice developed hepatic macrovesicular steatosis, which was confirmed by a higher liver concentration of triglycerides and increased expression of genes involved in de-novo lipogenesis. Pyrosequencing of the 16S ribosomal RNA genes revealed that RR and NRR mice had distinct gut microbiota including differences at the phylum, genera and species levels. Conclusions: Differences in microbiota composition can determine response to a HFD in mice. These results further demonstrate that the gut microbiota contributes to the development of NAFLD independently of obesity.